Still Down : What to Do When Antidepressants Fail - MacKinnon, Dean F. (Book collections on Project MUSE., 2016)
"Many people have depression symptoms that resist treatment. Despite medications, psychotherapy, and sometimes electroconvulsive therapy, these people don't feel well. What can they do to feel better? Dr. Dean MacKinnon, a psychiatrist at Johns Hopkins Hospital in Baltimore, specializes in finding out why treatment hasn't been helpful for a patient, and in helping that patient feel better. In Still Down, Dr. MacKinnon uses case studies of such individuals to reassess treatment-resistant depression (TRD) and explore what's going on with people who don't feel better, even with treatment. As some of the cases illustrate, some people who have been diagnosed with treatment-resistant depression have depression that actually will respond to appropriate treatment--but they have not yet received appropriate treatment. Other cases illustrate what happens when someone is incorrectly diagnosed with depression; that person needs treatment for a different disorder, not for depression. Finally, some cases illustrate people who have depression that does not respond to treatment for depression, regardless of how finely tuned the treatment is. These people, who have true TRD, can benefit from a variety of treatments alone or in combination, and even though they may not feel entirely well, they can feel better. Writing for people who have treatment-resistant depression and their families, as well as medical professionals and mental health care providers, MacKinnon hopes to help people with depression get appropriate diagnoses and treatment. He also hopes to improve care providers' understanding of treatment-resistant depression, by identifying aspects of the individual's qualities, behaviors, and experiences that may account for poor response to treatment"--